STRATEGI PEMBELAJARAN SENI TARI PADA ANAK DISABILITAS PADA SANGGAR SEKAR DEWATA DESA SERONGGA KECAMATAN GIANYAR KABUPATEN GIANYAR - Ni Nyoman Wahyu Adi Gotama; Komang Agus Triadi Kiswara (WIDYANATYA, 2019)
Disability is an inability of the body to carry out certain activities or activities as normal people in general are caused by a condition of disability in terms of physiological, psychological and structural abnormalities or anatomic functions. Disability was formerly better known by people as people with disabilities. then the Sekar Dewata dance studio in Serongga village, gianyar district took an action to restore the social function of children with disabilities in this study examines three things, namely 1) why an important strategy in dance learning is violated by sekar dewata village, Serongga village, Serongga district, Kab.gianyar2) dance learning strategies for children with disabilities violated by sekar dewata? 3) what are the implications of implementing the senitari learning strategy at Sanggara Sekar Deawata? This study uses qualitative research methods where data collected in the form of words. Theories used in this study are 1) Phenomenology theory 2) Structural functional theory 3) Behaviorism theory. The results of this study are 1) the importance of the role of strategy in learning dance in Sanggar Sekar Dewata are a. Cultural reasons see that dance art is an activity that is very closely related to Balinese life both in social and religious life. B. human social reasons are challenged as social creatures so to restore the social function is needed a plan (strategy) c. economic reasons where the skills possessed by children with disabilities can be an economic bridge. 2 How is the application of dance learning that is divided into several sub. A. the process of introducing various types of dance b. determining the type of dance to be given. C. basic training in a dance. D. dance learning in its entirety. The process is also supported by internal and external factors. 3. The method used is a method. demonstration method, 2. Driil method. 3. Is the method of imitation.